Lymphoepithelial Cysts of the Pancreas. Can Preoperative Imaging Distinguish This Benign Lesion from Malignant or Pre-Malignant Cystic Pancreatic Lesions? - Kavuturu, Srinivas; Sarwani, Nabeel E; Ruggeiro, Fransesca M; Deshaies, Isabelle; Kimchi, Eric T; Kaifi, Jussuf T; Staveley-O’Carroll, Kevin F; Gusani, Niraj J (JOP. Journal of the Pancreas, 2013)
Context Lymphoepithelial cysts of the pancreas are rare true benign cystic tumors of the pancreas of uncertain etiology. Cystic neoplasms of the pancreas present a significant diagnostic dilemma in differentiating benign from premalignant or malignant variants. Since the first description of lymphoepithelial cysts in 1985, 109 cases have been reported in the literature. We describe 6 cases of this rare tumor, the preoperative imaging results, and a review the literature. Patients Five males and one female ranging in age from 47 to 76 years underwent resection for lymphoepithelial cysts. Five patients presented with abdominal pain related to the lesion and in one patient the lesion was discovered incidentally. Four patients had elevated serum CA 19-9 levels. Pre-operative imaging with a CT scan and MRI of the abdomen typically revealed a well defined hypodense mass with Hounsfield units (HU) in the range of 15 to 20. One patient had papillary projections into the lesion. The mean size was 3.3 cm (ranging from 1.8 cm to 4 cm). All lesions were exophytic off the pancreatic parenchyma (1 cyst was located in the head of the pancreas, 2 were in the body, and 3 were in the tail region). Pre-operative EUS-guided/CT-guided needle aspiration, when performed, was not diagnostic. All patients underwent resection (one pancreaticoduodenectomy, five left pancreatectomies) to remove these cystic neoplasms. Pathology revealed a cyst lined by non-dysplastic squamous cells surrounded by sheets of benign lymphocytes. No evidence of malignancy was found. Conclusion Lymphoepithelial cysts of the pancreas are rare and are characteristically seen in men. While a hypodense mass (less than 20 HU) with papillary projections should be considered suspicious for lymphoepithelial cyst, a definitive diagnosis cannot be made solely based on preoperative imaging. EUS-guided biopsy coupled with biochemical/tumor marker studies are increasingly being used as a diagnostic tool to help differentiate between the various types of cystic pancreatic neoplasms. Imaging findings of lymphoepithelial cysts are non-specific and hence surgical resection is often required to rule out the presence of a malignant or pre-malignant cystic pancreatic lesion. In true lymphoepithelial cysts, malignant transformation is not seen and patients who have these cysts are not at increased risk of developing a pancreatic malignancy. Image: T1 post-contrast subtraction imaging shows the mass having a black non-enhancing center, with a thin rim of peripheral enhancement.